2008
DOI: 10.1897/07-315.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diazinon on larvae of the Asian common toad (Bufo melanostictus, Schneider 1799)

Abstract: Continuous subchronic exposure experiments were conducted to assess the effects of diazinon, an organophosphate pesticide, on the survival, growth and activity of larvae of the Asian common toad Bufo melanostictus. Two larval stages, the gill stage (Gosner stages 21 and 22) and gill-atrophy stage (Gosner stages 24 and 25), were continuously exposed to 4 microg/L, 400 mirog/L, and 10 mg/L of commercial-grade diazinon for 30 d. Treatments and untreated controls were maintained in triplicate with water changed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Lefcort et al (1999) reported such abnormal swimming in tadpoles of R. luteiventris exposed to heavy metals. Sumanadasa et al (2008) observed that diazinon also impaired swimming activity in tadpoles of the same species of toad as was used in the present study. Reduced swimming in tadpoles exposed to Cd could be attributed to several factors; Cd accumulation has been shown to occur in muscles, probably resulting in muscle damage (Vinodhini and Narayanan 2008).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Lefcort et al (1999) reported such abnormal swimming in tadpoles of R. luteiventris exposed to heavy metals. Sumanadasa et al (2008) observed that diazinon also impaired swimming activity in tadpoles of the same species of toad as was used in the present study. Reduced swimming in tadpoles exposed to Cd could be attributed to several factors; Cd accumulation has been shown to occur in muscles, probably resulting in muscle damage (Vinodhini and Narayanan 2008).…”
Section: Resultssupporting
confidence: 69%
“…The 10-day exposure trials were conducted in glass tanks of 22 9 15 9 15 cm containing 2 L of aged tap water (Sumanadasa et al 2008). Appropriate volumes of the stock solution were added to each tank to obtain the relevant test concentration and mixed well to ensure homogeneity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality in each tank was monitored daily and body length measurements, staging (according to Gosner, 1960) and recording of swimming activity were conducted on Day 1 and Day 4. Swimming activity was assessed using a protocol described by Sumanadasa et al (2008). Qualitative assessments were made of the abnormalities observed in the tadpoles.…”
Section: Methodsmentioning
confidence: 99%